The swing-by effect in the Vesta-Magnya case. Single and multiple encounters. - Araujo, Rosana A.N. [UNESP]; Winter, Othon C. [UNESP]; De A. Prado, Antônio F. B. (My University, 2012)
It was verified that the asteroid Magnya has some physical and chemical characteristics similar to the bodies from Vesta family. However, astronomical observations revealed that Magnya is distant from these bodies. In the present work, we assumed that Magnya originated from Vesta and we try to justify its current distant orbital location taking into account the effects of close encounters between Magnya and Vesta. The methodology adopted involved an analytical approach considering the technique of the gravity assisted maneuver, also known as swing-by. We found that the energy variation achieved through a single swing-by between Vesta and Magnya are very small when compared to the variation that would be required to change the orbit of Magnya. The effects of multiple close encounters were also considered and discussed. We concluded that the possibility of multiple encounters is limited, and therefore, that Magnya should suffer other perturbations (such as resonances, collisions or close encounters with other bodies, for instance) that would provide the supposed change in its orbit.
Keywords: Close encounter; Magnya; Swing-by; Vesta; Analytical approach; Astronomical observation; Energy variations; Gravity-assisted; Orbital locations; Physical and chemical characteristics; Swing by; Computer applications; Systems science; Asteroids